2003
DOI: 10.1373/49.4.644
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fasting Plasma Insulin, Free Fatty Acids, and Glucose Concentrations and of Homeostasis Model Assessment of Insulin Resistance in a Representative Sample of Quebec Children and Adolescents

Abstract: Background: Plasma fasting insulin and the homeostasis model assessment of insulin resistance (HOMA-IR) are markers of IR, which, at least in part, mediates the relation of obesity to increased cardiovascular risk. Increased free fatty acids (FFAs) may be involved in the pathogenesis of IR. Our objectives were to describe the distributions of fasting plasma insulin, glucose, and FFAs and HOMA-IR in youth and to assess the relationship between FFAs and markers of IR. Methods: Fasting plasma insulin, glucose, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
125
1
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 28 publications
12
125
1
10
Order By: Relevance
“…However, the absence of an association between FFA levels and insulin sensitivity is in line with two previous studies in children. These studies demonstrated that FFA levels were not associated with insulin sensitivity as estimated from fasting insulin and glucose levels (24)(25)(26). In addition, it should be pointed out that we did not observe any improvement in the association between QUICKI and clamp-derived insulin sensitivity after the incorporation of FFA levels.…”
Section: Discussionmentioning
confidence: 62%
“…However, the absence of an association between FFA levels and insulin sensitivity is in line with two previous studies in children. These studies demonstrated that FFA levels were not associated with insulin sensitivity as estimated from fasting insulin and glucose levels (24)(25)(26). In addition, it should be pointed out that we did not observe any improvement in the association between QUICKI and clamp-derived insulin sensitivity after the incorporation of FFA levels.…”
Section: Discussionmentioning
confidence: 62%
“…En esta muestra las mujeres presentaron mayor insulinemia y HOMA que los hombres, dimorfi smo reportado antes, aunque no siempre considerando la maduración puberal [24][25][26][27][28][29][30] . Verifi camos que la diferencia por sexo es independiente de la pubertad y que el aumento de ambos parámetros con la edad depende de la pubertad, ya que en la regresión múltiple la edad no fue signifi cativa.…”
Section: Discussionunclassified
“…Verifi camos que la diferencia por sexo es independiente de la pubertad y que el aumento de ambos parámetros con la edad depende de la pubertad, ya que en la regresión múltiple la edad no fue signifi cativa. La diferencia por sexo podría deberse a diferencias en estado nutricional, composición corporal o a un desfase temporal del "estirón" de talla 24,25 . La primera se descarta por ser todos eutrófi cos y sin diferencia de zIMC según sexo, aunque sí encontramos diferencia en zT/E y en %MG.…”
Section: Discussionunclassified
“…[15][16][17][18][19][20][21][22][23] This sex difference in insulin resistance has usually been attributed to differences in adiposity or pubertal stage, but in studies which have adjusted for these factors 15,18 a residual difference remains which has not been explained. We have shown that girls are substantially (B33%) more insulin resistant than boys at 5 years 24 and in the years leading up to puberty.…”
Section: Introductionmentioning
confidence: 99%